Maize metabolomics in relation to cropping system and growing year - Mattoo, Autar K.; Cavigelli, Michel A.; Mišić, Danijela M.; Gašić, Uroš; Maksimović, Vuk M.; Kramer, Matthew; Kaur, Bhavneet; Matekalo, Dragana; Nestorović Živković, Jasmina; Roberts, Daniel P. (Frontiers in Sustainable Food Systems, 2023)
Maize is important to global food security, being one of the predominant cereals in human and domesticated livestock diets worldwide. Due to the increasing human population, it will be important to not only design cropping systems to increase maize yield and sustainability but also to improve the nutritional quality of maize edible tissues. To determine cropping system impacts on maize grain nutritional content, we sampled grain from conventional and organic maize varieties grown for three growing seasons using five cropping systems. We analyzed the grain using metabolic fingerprinting of methanol extracts with ultra-high performance liquid chromatography (UHPLC) coupled with mass spectrometry (MS), adopting both non-targeted and targeted approaches. The cropping systems are part of a long-term study at the Beltsville Agricultural Research Center in Beltsville, Maryland, and were a three-year conventional no-till rotation (NT), a three-year conventional chisel-till rotation (CT), a two-year organic rotation (Org2), a three-year organic rotation (Org3), and a six-year organic rotation (Org6). Each cropping system had been in place for at least 10 years, allowing specific cropping-system-induced alterations of soil edaphic and microbial properties. Non-targeted metabolic fingerprinting detected a total of 90 compounds, the majority of which were phenolics. Metabolic profiling was further targeted toward 15 phenolics, 1 phytohormone, 7 carbohydrates and 7 organic acids, which were quantified in the maize grain originating from the five cropping systems. Statistical analysis of this subset of quantitative data determined that cropping system can significantly influence levels of certain maize grain metabolites. However, natural impacts (growing year) were substantially greater than cropping system impacts, likely masking or over-riding some cropping system impacts. Additionally, maize cultivar genetics had greater impact than cropping system on the maize grain metabolome and was the greatest “managed” impact on the metabolite profiles. Results indicate that until natural environmental impacts on maize grain metabolite levels are understood and managed, the best approach to reliably increase maize grain nutritional quality is through development of maize cultivars with enhanced nutritional content that are robust to natural environmental influence.